2019
DOI: 10.1094/pdis-09-18-1517-re
|View full text |Cite
|
Sign up to set email alerts
|

Control of Wheat Fusarium Head Blight by Heat-Stable Antifungal Factor (HSAF) from Lysobacter enzymogenes

Abstract: Heat-stable antifungal factor (HSAF), which belongs to the polycyclic tetramate macrolactam family, was isolated from Lysobacter enzymogenes fermentations and exhibited inhibitory activities against a wide range of fungal pathogens. In this study, the antifungal activity of HSAF against Fusarium graminearum in vitro and in vivo was investigated. A total of 50% of mycelial growth of F. graminearum was suppressed with 4.1 μg/ml of HSAF (EC50 value). HSAF treatment resulted in abnormal morphology of the hyphae, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…The EC 50 for mycelium growth in C. fructicola is 0.43 mg L −1 , which is equivalent to many chemical fungicides such as propiconazole, bitertanol, imazalil and hexaconazole as reported by de los Santos García de Paredes 36 . In this study, HSAF‐treated C. fructicola hyphae showed deformities, such as hyperbranching, curling, swelling and depolarized growth, similar to those reported previously in A. nidulans and F. graminearum 16,22 . Thus, HSAF may have a conservative mode of action that affects the growth of filamentous hyphae.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The EC 50 for mycelium growth in C. fructicola is 0.43 mg L −1 , which is equivalent to many chemical fungicides such as propiconazole, bitertanol, imazalil and hexaconazole as reported by de los Santos García de Paredes 36 . In this study, HSAF‐treated C. fructicola hyphae showed deformities, such as hyperbranching, curling, swelling and depolarized growth, similar to those reported previously in A. nidulans and F. graminearum 16,22 . Thus, HSAF may have a conservative mode of action that affects the growth of filamentous hyphae.…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, L. enzymogenes C3 (HSAF‐producing strain) has been shown to have field efficacy against Bipolaris sorokiniana , causing Bipolaris leaf spot in turf grasses 21 . Recently, HSAF was also found to have good biocontrol against wheat head blight caused by Fusarium graminearum in field experiments 22 . However, there has been no detailed study of the antifungal effect of HSAF against Colletotrichum spp.…”
Section: Introductionmentioning
confidence: 99%
“…Lysobacter enzymogenes is a nonpathogenic strain that was used to control crop fungal diseases known for the synthesis of an antifungal weapon (heat-stable antifungal factor, HSAF) that exhibits inhibitory activity against a wide range of fungal species [16][17][18][19][20][21][22][23] . Our previous work revealed that RpfG affects production of the antifungal weapon HSAF in L. enzymogenes 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Lysobacter enzymogenes (Le) strain OH11, originally isolated from the rhizosphere of green pepper, is a nonpathogenic strain that was used to control crop fungal diseases (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Heat-stable antifungal factor (HSAF), a polycyclic tetramate macrolactam, is a newly identified broad-spectrum antifungal antibiotic isolated from the biocontrol species L. enzymogenes and is regarded as an attractive agent for the biological control of fungal diseases of agriculturally important plants (5)(6)(7)(8). HSAF exhibits inhibitory activity against a wide range of fungal species, and its chemical structure and mode of action are distinct from those of existing antifungal drugs or fungicides (1,7). Therefore, the identification of genes and growth conditions that regulate HSAF production is of significant interest.…”
Section: Introductionmentioning
confidence: 99%